Perbedaan Tasawuf dengan Teologi dan Fiqh - Rossyka, Maqhfira Maulia (Maliki Interdisciplinary Journal, 2024)
Islam is a religion that has the blessing of diversity in scientific studies. There are three fields of scientific discipline, namely: Sufism, Theology (kalam), and Fiqh. These three fields have given birth to various views, opinions and schools. It is very important to discuss this area of ​​scientific discipline in order to better understand and know the differences that exist and have advantages in terms of increasing Islamic insight in dealing with differences among the people. The purpose of this discussion is to analyze the differences between Sufism, theology and Fiqh using the perspective of objects, goals and methods as well as their implications in building Islamic brotherhood and achieving mutual benefit. Based on the results of this article, it can be concluded that there are differences between Sufism, theology and Fiqh in terms of objects, objectives and methods. These three scientific disciplines have different characteristics and essence.